PENGARUH FINANCIAL DISTRESS DAN CAPITAL INTENSITY TERHADAP TAX AVOIDANCE DENGAN UKURAN PERUSAHAAN SEBAGAI PEMODERASI - Julianty, Indira; Agung Ulupui, I Gusti Ketut; Nasution, Hafifah (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2023)
The decline in tax performance during the Covid-19 pandemic is the reason for conducting this study, namely to find out whether tax avoidance activities are increasingly being carried out, especially in the consumer non-cyclicals and consumer cyclicals sectors during the 2020-2022 period. This study is also intended to confirm the inconsistency in the relationship between financial distress and capital intensity on tax avoidance by presenting moderating variables in the form of firm size as a novelty from previous research. Using the absolute difference value test, this study shows that financial distress has a negative effect on tax avoidance, while capital intensity and firm size do not affect tax avoidance. In addition, the effect of financial distress and capital intensity on tax avoidance cannot be moderated by firm size. The implications of this study indicate the need for increased supervision from the government and shareholders on management to avoid tax avoidance, especially in companies that are financially healthy.